Multidomain interventions for non-pharmacological enhancement (MINE) program in Chinese older adults with mild cognitive impairment: a multicenter randomized controlled trial protocol - Xiaochu Wu; Tianyao Zhang; Yanhao Tu; Xueling Deng; A Sigen; Yuxiao Li; Xiaofan Jing; Lixuan Wei; Ning Huang; Ying Cheng; Linghui Deng; Shuli Jia; et al. (BMC Neurology, 2023)
Abstract Background Dementia is characterized by progressive neurodegeneration and therefore early intervention could have the best chance of preserving brain health. There are significant differences in health awareness, living customs, and daily behaviors among Chinese older adults compared to Europeans and Americans. Because the synergistic benefits of multidomain non-pharmacological interventions are consistent with the multifactorial pathogenicity of MCI, such interventions are more appealing, easier to adhere to, and more relevant to daily life than single-mode interventions. One of the aims of this study is to verify the effect of multidomain intervention strategies for MCI patients based on Chinese population characteristics, and the other is to establish a biobank and image database to investigate the pathogenesis and pathways of cognitive impairment. Methods Our study was designed as a national multicenter, community-based randomized controlled trial (RCT). Twelve medical institutions in ten Chinese cities will participate in our study from 2020 to 2024, and 1080 community residents aged 50 and above will be enrolled as participants. Each sub-center will be responsible for 90 participants (30 people per community) across three communities (non-contact control group, health education group, and multidomain intervention group). The community will be the basic unit of the present study, and all participants in each community will receive the same intervention/control measure. Three working groups are set up in each sub-center to manage the three communities independently to minimize interference at the implementation level between the groups. The multidomain intervention group will receive integrated interventions including exercise, nutrition, sleep, health education and mindfulness meditation. All data generated by the research will be analyzed and processed by statistical software (such as SPSS 21.0, Python 3.0, etc.), and part of the research data will be displayed in the form of graphs and tables. Discussion In order to achieve a high-quality community intervention study, it is crucial to have a well-designed experimental protocol that follows rigorous scientific methodology. In addition, effective management of quality control measures and monitoring compliance throughout the study process are essential components. This study provides a detailed discussion of stakeholder compliance, research quality control, potential harm and mitigation, auditing, and future plans in order to better address research issues. Trial registration : ChiCTR2000035012 (July 27, 2020).